The Application of Image Sharpening and Wiener Methods to Improve the Quality of Lung X-ray Images: Application of Image Sharpening and Wiener Methods to Improve the Quality of Lung X-ray Images - Sriani; Hasugian, Abdul Halim; Nasution, Yurika (Bahasa Indonesia, 2023)
Medical imaging is a process of visual representation of several functions of human organs whichs used for clinical diagnosis, medical treatment, suchs x-rays which are a form of electromagnetic radiation that penetrates the human body and has the result of images of human organs like shadows on special black x-ray paper with the aim of knowing the condition human organs, suchs healthy or unhealthy lung conditions. However, lung x-ray results can provide different results from the original because they have poor quality caused by noise, blurred colors and so on, making them difficult for humans to interpret. Therefore, it’s necessary to carry out an image processing process in order to improve image quality using sharpening or getting an image display with a better form of visualization. One of the techniques used in sharpening is the Wiener filter whichs a process of improving image restoration from blurry effects based on least squares. The average percentage results that occur after applying the sharpening and Wiener methods to blurred images are 67.30%, with an average difference of 32.69%.